Playing by the rules: rewriting as a practical optimisation technique in GHC - Peyton Jones, Simon; Tolmach, Andrew; Hoare, Tony (2001 Haskell Workshop, 2001)
We describe a facility for improving optimization of Haskell programs using rewrite rules. Library authors can use rules to express domain-specific optimizations that the compiler cannot discover for itself. The compiler can also generate rules internally to propagate information obtained from automated analyses. The rewrite mechanism is fully implemented in the released Glasgow Haskell Compiler. Our system is very simple, but can be effective in optimizing real programs. We describe two practical applications involving short-cut deforestation, for lists and for rose trees, and document substantial performance improvements on a range of programs.